Pelatihan Desain Grafis Menggunakan Canva untuk Para Peserta LTQ Al Mubar - Juliasari, Noni; mulyati, sri; Amini, Safrina (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2025)
Al Mubar Quran Tahfidz Institute is an organization founded in 2009 with the mission of promoting da’wah and teaching the Quran in the Karang Tengah area and its surroundings. Its primary focus is to improve Quranic reading through tahsin activities and to assist both children and adults in memorizing the Quran. However, with the rapid technological advancements of today, enhancing digital literacy within the community has become an essential necessity. LTQ Al Mubar also seeks to contribute to the improvement of knowledge and skills in this digital era by providing graphic design training using the Canva application, which is part of their initiative to enhance digital literacy among community members. Participants in this training will acquire skills to create graphic designs suitable for promotional media, enabling them to convey effective and engaging information about products, services, or activities to the broader community. This community service approach employs both lecture and practical methods. The graphic design curriculum includes lessons on creating greeting cards, flyers, and blog banners. Evaluation results from the graphic design training using Canva indicate that 65% of respondents strongly agree that the training materials were presented clearly, while 55% strongly agree that they were given opportunities to ask questions and received satisfactory answers from the instructor. Regarding the training facilities, 60% of respondents strongly agree that they were adequately provided, and ultimately, 75% of respondents strongly agree, while another 25% agree that this training has been beneficial for them.